2008
DOI: 10.21608/eajbsa.2008.15725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flufenoxuron on the antennal sensilla of Spodoptera littoralis (Lepidoptera: Noctuidae).

Abstract: In the present study, the effect of flufenoxuron on the sensory organ in the antenna of Spodoptera littoralis was showed after feeding of the 3 rd larval instars for 24 hrs. on treated castor been leaves with Lc 50 . Each adult antenna, male and female of untreated and treated group is divided into about 77-82 segment like annuli; and each segment is divided into a sensory region containing the olfactory sensilla and a largely non-sensory region containing scales and a very small number of sensory structures.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…Besides, some pores appeared in sensilla basiconica .These abnormalities may be attributed to the effect of insect growth regulator indirectly on the release of ecdysteroids, through interfering with the neuroendocrine sites responsible for the release of this hormone. In agreement with Zohry (2008) who revealed that LC 50 of flufenoxuron caused the formation of abnormal antennae and affect the length and distribution of the sensilla on Spodoptera littoralis. Similarly, Schmutterer et al, (1993) observed morphogenetic defects on antennae due to treatments of nymphs of desert locust, Schistocerca gregaria and the red locust, Nomadacris septemfasciata with neem oil.…”
Section: Discussionsupporting
confidence: 89%
“…Besides, some pores appeared in sensilla basiconica .These abnormalities may be attributed to the effect of insect growth regulator indirectly on the release of ecdysteroids, through interfering with the neuroendocrine sites responsible for the release of this hormone. In agreement with Zohry (2008) who revealed that LC 50 of flufenoxuron caused the formation of abnormal antennae and affect the length and distribution of the sensilla on Spodoptera littoralis. Similarly, Schmutterer et al, (1993) observed morphogenetic defects on antennae due to treatments of nymphs of desert locust, Schistocerca gregaria and the red locust, Nomadacris septemfasciata with neem oil.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand female adult antennae resulted from treated 4 th larval instar with LC 50 of Atabron showed antennae with highly confused segments without sensillae as shown in Plate (2-b) and the last three segments confused but without sensillae as shown in Plate (2-d). Similarily, obtained by Zohry (2008) who revealed that LC 50 of flufenoxuron on 3 rd larval instar of Spodoptera littoralis caused the formation of abnormal antennae and affect the length and distribution of sensillae.…”
Section: Effect Of Chlorfluazuron On the Antennal Sensilla Of Adult Fsupporting
confidence: 85%
“…1970 , Flower and Helson 1974 , Liu and Liu 1984 , Lavoie-Dornik and McNeil 1987 , Castrejón-Gómez et al. 1999 , Zohry 2008 , Diongue et al. 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…2013 ), and S. littoralis ( Seada 2015 ). Pores were observed on the tip indicated their chemoreceptor function, and in fact, Flower and Helson (1974) and Zohry (2008) called this sensillum as “taste rod.”…”
Section: Discussionmentioning
confidence: 99%